Lithiation of the diaminopyridine protio-ligand MeC(2-C5H4N){CH2N(H) Mes}(2) (Mes=2,4,6-C6H2Me3) - Ward, B; Gade, L; Mountford, P (2006)
Reaction of the diamidopyridine protio-ligand MeC(2-C5H 4N){CH2N(H)Mes}2 (Mes = 2,4,6-C 6H2Me3) with butyllithium in diethyl ether affords the compound (diethyl ether)(μ4-2-{6-[1,3-dimethyl-3-(2- pyridyl)-1,4-bis(2,4,6-trimethylanilinio)butyl]-2-pyridyl}-2-methyl-1,3-bis(2,4, 6-trimethylanilinio)propane)tetralithium(I), [Li4(C 55H64N6)(C4 H10O)] or Li4[MeC(2-C5H4N){CH2N(Mes)}CHN(2,4, 6-C6H2-Me2C(Me)(2,2′-C5H 3N){C(Me)}(CH2NMes)2](OEt2), which shows the methylation of the pyridyl ortho-position with a methyl group of one of the mesityl groups. The complex contains four Li atoms, each of which is chemically distinct. The tetraanionic ligand contains two protio-ligand units which are fused together into a single entity. The structure contains two disordered molecules of diethyl ether, one of which is coordinated to one of the Li atoms. © 2006 International Union of Crystallography All rights reserved.